14.EXPERIMENTAL EVALUATION OF SKIN IRRITATION OF SPRAY SOLUTION USED IN THE TREATMENT OF WOUND INJURIES ON SKIN CONTAINING NANO SILVER AND SOME HERBAL MEDICINES (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate on skin irritatinon of spray solution used in the treatment of wound injuries on skin containing nano silver and some herbals (Coptis lonicera, polygonum, turmeric).Method: The methodological research was carried out according to the guidelines of OECD and the Ministry of Health. The gauze patch of 0.5g solution was applied to the appropriate healthy skin of 15 rabbits; after 4 hours by peeling off gauze and cleaning. Evaluation of activation index at 24, 48 and 72h after cleaning.Results: The application index was 0 (no erythema, scab formation and edema in healthy rabbit skin).Conclusions: The product does not cause skin irritation on experimental animals.
Keywords: Spray solution used in the treatment of wound injuries; rabbis; skin irritation